Microstructural characterization of Cu2ZnSn(S, Se)4 solar cells fabricated from nanoparticles. (7th July 2015) - Zhang, Yiwen; Suyama, Naoki; Goto, Masanori; Kuwana, Jun; Sugimoto, Kanta; Satake, Tetsuo; Kurokawa, Yasuyoshi; Yin, Ming; Yamada, Akira
Abstract: We characterized the microstructure of Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells fabricated from Cu-poor, Zn-rich Cu2 ZnSnSe4 (CZTSe) nanoparticles. Various sintering atmospheres of sulfur and selenium led to different microstructural properties. For the samples sintered under sulfur atmosphere, a large number of ZnS secondary phases were observed and the Zn/Sn ratio of the grains was significantly lower than 1. Regions of the ZnS secondary phases showed a dark contrast in electron-beam-induced current (EBIC) images, indicating that the existence of the ZnS phases reduced the minority carrier collection efficiency. In contrast, for the samples sintered under selenium atmosphere, Cu was found to accumulate near the grain boundaries to form the Cu-rich CZTSe phases and only a small number of ZnSe secondary phases were detected.